2000
DOI: 10.2527/2000.78150x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of birth weight and postnatal nutrition on neonatal sheep: II. Skeletal muscle growth and development.

Abstract: This study investigated effects of birth weight and postnatal nutrition on growth and development of skeletal muscles in neonatal lambs. Low (L; mean +/- SD 2.289 +/- .341 kg, n = 28) and high (H; 4.840 +/- .446 kg, n = 20) birth weight male Suffolk x (Finnsheep x Dorset) lambs were individually reared on a liquid diet to grow rapidly (ad libitum fed, ADG 337 g, n = 20) or slowly (ADG 150 g, n = 20) from birth to live weights (LW) up to approximately 20 kg. At birth, weight of semitendinosus (ST) muscle in L l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
119
3
15

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(148 citation statements)
references
References 28 publications
11
119
3
15
Order By: Relevance
“…This concept implies that a stimulus or insult acting during critical periods of growth and development may result in developmental adaptations that permanently change the structure, physiology and metabolism of the offspring (Barker, 1995). Maternal undernutrition may impact upon offsprings' growth efficiency and body composition (Greenwood et al, 2000;Caton et al, 2009) and is crucial for both skeletal muscle (Greenwood et al, 2000) and adipose tissue development (Taylor and Poston, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…This concept implies that a stimulus or insult acting during critical periods of growth and development may result in developmental adaptations that permanently change the structure, physiology and metabolism of the offspring (Barker, 1995). Maternal undernutrition may impact upon offsprings' growth efficiency and body composition (Greenwood et al, 2000;Caton et al, 2009) and is crucial for both skeletal muscle (Greenwood et al, 2000) and adipose tissue development (Taylor and Poston, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In cattle, fetal growth restriction to about half normal growth during the period 232-271 days of gestation resulted in a 7.8% increase in muscle DNA content, compared with a 99.5% increase during normal fetal growth (Ferrell 1991). In this regard, it has been demonstrated that the number of satellite cells , replication of satellite cell nuclei (Greenwood et al 1999b) and subsequent accumulation of muscle DNA (Robinson 1969;Beermann 1983;Greenwood et al 2000) can be reduced by prenatal and/or early postnatal growth retardation with potential longer-term consequences for growth, body composition and body size (Widdowson 1971;Greenwood et al 1998).…”
Section: Musclementioning
confidence: 99%
“…In ruminants, the influence of growth retardation on subsequent growth and development is important during late gestation (Everitt 1967;Greenwood et al 1998Greenwood et al , 1999bGreenwood et al , 2000. It has been demonstrated in various species that the number of myonuclei or the DNA content in muscle can be reduced by undernutrition during early life, but this influence diminishes as the age when the nutritional restriction is .…”
Section: Musclementioning
confidence: 99%
See 2 more Smart Citations